Validity and reliability evidence for motor competence assessments in children and adolescents: A systematic review. Issue 15 (2nd August 2020) - Hulteen, Ryan M.; Barnett, Lisa M.; True, Larissa; Lander, Natalie J.; del Pozo Cruz, Borja; Lonsdale, Chris
ABSTRACT: Valid and reliable tests of motor competence are necessary to allow researchers and practitioners to quantify levels of motor competence, identify skill deficiencies, and determine the effectiveness of motor skill interventions. The primary study aim was to systematically review the validity and reliability of scores derived from gross motor competence tests for typically developing child and adolescent populations. The secondary aim of this review was to identify the most prevalent motor skills assessed across all instruments. A search of seven electronic databases identified 57 different skill assessment tools from 107 studies. Construct validity was the most common measurement property examined (60 studies; 56%). Content validity (21 studies; 20%) was the least commonly explored measurement property. Scores derived from the Test of Gross Motor Development – second and third edition had the most support for validity and reliability. The most common skills included in these skill batteries were the overhand throw (n = 33), catch (n = 32), jump (n = 31) and hop (n = 26). Research efforts should focus on: (1) further investigation of measurement properties of existing tools rather than developing new assessments and (2) further investigation of existing tools and their measurement properties in adolescent populations.